2014
DOI: 10.1515/htmp-2013-0118
|View full text |Cite
|
Sign up to set email alerts
|

Separation of ZnO from the Stainless Steelmaking Dust and Graphite Mixture by Microwave Irradiation

Abstract: In this study, microwave was used to treat stainless steelmaking dust containing zinc oxide. The effects of heating time, carbon content and zinc oxide content on the removal efficiency of zinc oxide and the reduction efficiency of iron oxide were investigated. Experimental results show that, for the sample with 16% (mass percent, the same below) graphite heated for 10 minutes by 10 kW power microwave, the removal efficiency of zinc oxide is between 80% and 90% and the metallization ratio of iron oxide is betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…A similar behavior can be observed in the reaction with dissolved carbon listed in (3). A high C content in the iron bath increases the carbon activity and, therefore, the driving force for the reduction of ZnO [6,7,9,10,[17][18][19][20].…”
supporting
confidence: 71%
See 1 more Smart Citation
“…A similar behavior can be observed in the reaction with dissolved carbon listed in (3). A high C content in the iron bath increases the carbon activity and, therefore, the driving force for the reduction of ZnO [6,7,9,10,[17][18][19][20].…”
supporting
confidence: 71%
“…Sci. 2022, 12, 664 2 of 10 Therefore, ZnO*Fe 2 O 3 can be neglected at the trial process temperature described in this paper (1400 • C) [1,2,[6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A problem encountered in this approach, is the reaction of Fe3O4 in EAFD with the halogen acids, leading to the formation of iron chloride/bromide, which is carried over to the final leaching solution as Fe 2+ and impairs the extraction of zinc at a high purity [16,17,21]. Since these techniques require significant heat addition, much work has been directed towards studying the use of microwave energy as a heating source for the treatment of EAFD [16,17,[22][23][24][25][26][27]. Ye et al [27,28] reported the possibility of using microwaves for the carbothermic reduction of EAFD with biochar and identified the main heating mechanisms for the system.…”
Section: Introductionmentioning
confidence: 99%
“…20 Zhou et al and Kim et al also examined the reduction of zinc oxide from dust and found that the dezincification percentage reached 80%−90% rapidly under microwave irradiation. 21 These studies focused on the reduction behaviors of zinc and iron components, with little attention on the other valuable components, like Mn and Cr. Meanwhile, in-depth exploration of the microwave heating mechanism, which controls the reduction performance, 4 has not been carried out.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To intensify the reduction process, much attention has been devoted to the use of microwave heating for EAF dust treatment in recent years, considering its high thermal efficiency due to volumetric and selective heating features. , It was reported that under microwave irradiation the reduction of metal oxides in the dust could be accomplished in 20 min with a high dezincification percentage (92.79%) using blast furnace slag as the reduction agent . Zhou et al and Kim et al also examined the reduction of zinc oxide from dust and found that the dezincification percentage reached 80%–90% rapidly under microwave irradiation . These studies focused on the reduction behaviors of zinc and iron components, with little attention on the other valuable components, like Mn and Cr.…”
Section: Introductionmentioning
confidence: 99%